Nutritional changes in oilseeds due to Aspergillus spp. - Chavan*, Ashok M. (Journal of Experimental Sciences, 2011)
In present research work experiments were carried out to study the deteriorative changes in oilseeds under the influence of Aspergillus sp. It was found that fat content in groundnut and soybean was reduced due to Aspergillus flavus. In groundnut the maximum loss in protein content was due to A. terreus. On the other hand, A. niger, A. terreus, A. parasiticus and A. fumigatus were found to reduced the protein content in soybean. A. versicolor effectively reduced maximum amount of reducing sugar content in groundnut and soybean.